2019
DOI: 10.1161/circoutcomes.118.005273
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular-First Treatment Is Associated With Improved Amputation-Free Survival in Patients With Critical Limb Ischemia

Abstract: Background: Critical limb ischemia remains a difficult disease to treat, with limited level one data. The BEST-CLI trial (Best Endovascular vs Best Open Surgical Therapy in Patients with Critical Limb Ischemia) is attempting to answer whether initial treatment with open surgical bypass or endovascular therapy improves outcomes, although it remains in enrollment. This study aims to compare amputation-free survival and reintervention rates in patients treated with initial open surgical bypass or endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
3
36
0
2
Order By: Relevance
“…As reported in the SPINACH study, 10 better wound healing after surgical revascularization compared to EVT may be reflected in this better LBP for bypass surgery. However, a recent study comparing EVT and bypass surgery reported no significant differences in the limb salvage, amputationfree survival, or survival rates 15 ; it also reported that an EVT-first strategy improved limb salvage rates. In the present study, SPP was measured on the dorsal and plantar sides of the foot, which enabled evaluation of the ischemic conditions of the overall foot region, and the blood flow was found to be lower after EVT alone than after bypass surgery.…”
Section: Discussionmentioning
confidence: 97%
“…As reported in the SPINACH study, 10 better wound healing after surgical revascularization compared to EVT may be reflected in this better LBP for bypass surgery. However, a recent study comparing EVT and bypass surgery reported no significant differences in the limb salvage, amputationfree survival, or survival rates 15 ; it also reported that an EVT-first strategy improved limb salvage rates. In the present study, SPP was measured on the dorsal and plantar sides of the foot, which enabled evaluation of the ischemic conditions of the overall foot region, and the blood flow was found to be lower after EVT alone than after bypass surgery.…”
Section: Discussionmentioning
confidence: 97%
“… 30 Moreover, a recent study showed that patients initially treated with open surgery presented higher lower limb amputation rates than those treated with endovascular techniques. 33 The authors concluded that the choice for open surgery was possibly being made for those patients with PAD at more advanced stages when prognosis is poorer. Although the correlation between MLLA rates and endovascular procedures was also significantly positive, it was 40% lower than the correlation with open surgeries, in agreement with a previous study that suggested that patients undergoing endovascular treatment will evolve with fewer MLLA rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the correlation between MLLA rates and endovascular procedures was also significantly positive, it was 40% lower than the correlation with open surgeries, in agreement with a previous study that suggested that patients undergoing endovascular treatment will evolve with fewer MLLA rates. 33 …”
Section: Discussionmentioning
confidence: 99%
“…The weighted mean age-standardized prevalence and incidence of outpatient PAD in the USA have been recently estimated to be 11.8% and 22.4/1,000 person-years, respectively [2]. Minimal invasive endovascular treatment has become a mainstay in the treatment of PAD, due to high clinical success and low complication rates [3,4]. Especially for the management of critical limb ischemia (CLI), the most advanced stage of PAD which usually affects a more aged population with severe comorbidities and high surgical risk, endovascular treatment constitutes the best treatment option to avoid major limb amputation in significant percentages of everyday clinical practice [5,6].…”
Section: Introductionmentioning
confidence: 99%